Implementation of evidence-based parenting programs under real-world conditions: Protocol for a scoping review. - Rita Pinto; Catarina Canário; Orlanda Cruz; Maria José Rodrigo (PLoS ONE)
Protecting children is recognized as a public health priority and supporting parents through the implementation of evidence-based programs is a well-known strategy to achieve this. However, researchers highlight that these programs remain insufficiently implemented in real-world contexts. A knowledge gap exists between the intended implementation of evidence-based parenting programs and their actual implementation on real-world dynamics. This scoping review aims to provide a comprehensive understanding of how evidence-based parenting programs have been implemented under real-world conditions by providing a map of available evidence and identifying knowledge gaps. The overall research question is: "How have evidence-based parenting programs been implemented under real-world conditions?". The proposed scoping review follows the framework originally described by Arksey and O'Malley, Levac and colleagues, and the Joanna Briggs Institute: (1) identifying the research questions; (2) identifying the relevant studies; (3) study selection; (4) charting the data; (5) collating, summarizing, and reporting the results; (6) consultation. The Preferred Reporting Items for Systematic reviews and Meta-Analyses extension for Scoping Reviews (PRISMA-ScR) will inform the search strategy. The results will be described in relation to the research questions and in the context of the purpose of the review. This scoping review will help to bridge the implementation gap between research evidence and its translation into practice.